Produtividade comercial em sistemas de reprodução de tilápia do Nilo da linhagem GIFT - Wild, Monique Bayer (2013)
This study aimed to evaluate the productivity of Nile tilapia fingerlings of GIFT strain in different reproduction systems, as the area, the collection strategy of post-larvae, the hand labor and broodstock families used. The data collection of the harvest 2011/2012 was held at f Sgarbi fish farm, located in Palotina-PR, Brazil. The classification of the five reproduction systems occurred according the infrastructure and collection strategy used. The System I was characterized by masonry tanks with artificial nests and harvesting continuous partial post-larvae. The System II was made up of ponds wall covered in masonry with postlarvae partial continuous harvesting. Systems III and IV consisted of hapas with partial continuous harvesting of post-larvae and harvesting eggs in the mouth of females, respectively. In the System V was practiced the postlarvae continuous partial harvesting in ponds. The productivity was evaluated in function of the reproductive system, of the number of employees, and of the presence of employees amount, denominated for A, B, C, D, E and F. The productivity of eggs and larvae and the period of incubation of the eggs were also evaluated for broodstock families, called by FA, FB and FC. There were used analysis of unifactorial variance and covariance. The Systems III and IV were more productive (p<0.05), with approximately 7,000 fingerlings m-3, followed by the System I with approximately 2,700 fingerlings m-3 and Systems II and V, with an approximate average of 165 fingerlings m-3. In eggs harvesting in hapas the productivity was high at early (p<0.05), decreasing throughout of the period, while the opposite occurred for the harvesting postlarvae in hapas. In the System IV the productivity of fry obtained by two workers was higher (p<0.05) for the resulted for only one. The presence of the employee B resulted in a significant difference (p=0.04) in the productivity of System IV, while the presence of the employee and A in the System IV and of the employees C, D, E and F in the System V did not affect (p>0.05) the productivity of fingerlings. The reproductive efficiency, expressed in grams of eggs by kilogram of female was higher (p<0.05) for the broodstock family FC, however, no differences (p>0.05) between the broodstock families studied as to the number of fingerlings produced. The time to the onset of hatching was lower (p<0.05) for the broodstock family FA (1.5 to 2 days) compared to the others. The productivity of fingerlings is greater when hapas are used in the reproduction system, independent of harvesting strategy adopted. The productivity of fingerlings on a commercial scale can be improved due to hand-to-work of employees, but not in terms of broodstock families used in the fish farm assessed